Molecular identification of Malassezia species isolated from neonates hospitalized in Neonatal intensive care units and their mothers - Kamiar Zomorodian; Maryam Naderibeni; Hossein Mirhendi; Mostajab Razavi Nejad; Seyed Mojtaba Saneian; Mozhgan Mahmoodi; mahboobeh kharazi; Hossein Khodadadi; Keyvan Pakshir; Marjan Motamedi (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: Given the important role of Malassezia spp. in skin diseasesand other associated infections in neonates, this study aimed to investigate the presenceand frequency of Malassezia spp. in the skin of neonates hospitalized in neonatalintensive care units and their mothers using culture and accurate molecular-basedmethods.Materials and Methods: In total, 205 samples were collected from 130 neonates (>4-day-old) and 75 mothers. Isolation of Malassezia spp. from the skin was performed usingLeeming-Notman agar and modified Dixon agar media. To compare the Malasseziamicroflora on the skin of the neonates and their mothers, a polymerase chain reactionsequencing method was performed for spp. identification of 92 isolates obtained fromneonates and their mothers. Moreover, possible associated risk factors for thecolonization of Malassezia spp. on the skin were recorded.Results: Cultures from 62.3% of neonates and 77.3% of mothers were positive forMalassezia spp. growth. Malassezia globosa was the most prevalent isolated spp. foundin the skin of the study population. It is noteworthy that a rare Malassezia spp.,Malassezia arunalokei, was isolated from the skin of one neonate. There was a 76%similarity between the mother-neonate isolate sequences results. The statistical analysisshowed that the type of feeding is a significant (P<0.001) associated factor forMalassezia skin colonization.Conclusion: The findings support the hypothesis that the colonization of Malassezia inneonates is significantly influenced by that of the mother, and this may be associatedwith breastfeeding.